2020
DOI: 10.3892/etm.2020.9072
|View full text |Cite
|
Sign up to set email alerts
|

Rhodiola Crenulata ameliorates exhaustive exercise‑induced fatigue in mice by suppressing mitophagy in skeletal muscle

Abstract: The aim of present study was to evaluate the potential effects of Rhodiola crenulata oral liquid (RCOL) on exhaustive exercise (EE)-induced fatigue in mice. Male Institute of Cancer Research mice from five treatment groups (n=10 per group) were orally administered with sterilized water for the Control and EE groups and/or RCOL at doses of 1.02, 3.03 and 6.06 ml/kg/day, once daily for 2 weeks. Anti-fatigue activity was subsequently evaluated by measuring the levels of creatine kinase (CK), lactic acid (LA), lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 62 publications
(75 reference statements)
0
24
0
Order By: Relevance
“…This result indicated that LSF had a better antioxidant capacity than that of vitamin C. MDA is the oxidation product of cell membrane lipids and a sensitive index of lipid peroxidation. When fatigue occurs in the human body, the level of MDA increases accordingly (Hou et al, 2020). In this research, MDA levels in the vitamin C group and LSF group were significantly lower than those in the negative control group, and LSF supplementation reduced MDA levels in a dose-dependent manner, indicating that LSF can play a protective and antioxidant role by attenuating lipid peroxidation.…”
Section: Discussionsmentioning
confidence: 49%
“…This result indicated that LSF had a better antioxidant capacity than that of vitamin C. MDA is the oxidation product of cell membrane lipids and a sensitive index of lipid peroxidation. When fatigue occurs in the human body, the level of MDA increases accordingly (Hou et al, 2020). In this research, MDA levels in the vitamin C group and LSF group were significantly lower than those in the negative control group, and LSF supplementation reduced MDA levels in a dose-dependent manner, indicating that LSF can play a protective and antioxidant role by attenuating lipid peroxidation.…”
Section: Discussionsmentioning
confidence: 49%
“…The brain tissues of animal subject to CHH and AHH insults were collected for Western blot analysis ( Hou et al, 2020 ). The total protein of the brain tissue was extracted by a total protein extraction kit, and the total protein concentration was measured by a BCA protein quantitative kit.…”
Section: Methodsmentioning
confidence: 99%
“…nNOS protects tissues and nerve cells and can repair tissue damage caused by oxidative damage [ 35 ]. The expression of eNOS was relatively stable in tissues, and eNOS produces NO, which promotes the repair of liver damage caused by oxidative stress [ 36 ].…”
Section: Discussionmentioning
confidence: 99%